1999
DOI: 10.12968/bjcn.1999.4.10.7440
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an initiative: clinical supervision in a community health trust

Abstract: This article describes the implementation and evaluation of a pilot project for clinical supervision in a Community Health Trust involving health visitors, district nurses and clinic nurses. The project represented collaboration between educationalists, clinicians and managers interested in establishing a working and sustainable culture of clinical supervision. The article provides an overview of a small scale study designed to chart the process of an innovation to implement clinical supervision in the practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…We also found that supervisees have quite different experiences, and evaluations vary depending on previous experiences of CS, form and group size, frequency, duration and place of sessions (see also Draper et al. 1999, Edwards et al.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…We also found that supervisees have quite different experiences, and evaluations vary depending on previous experiences of CS, form and group size, frequency, duration and place of sessions (see also Draper et al. 1999, Edwards et al.…”
Section: Discussionmentioning
confidence: 70%
“…We also found that supervisees have quite different experiences, and evaluations vary depending on previous experiences of CS, form and group size, frequency, duration and place of sessions (see also Draper et al 1999, Edwards et al 2005. In our survey, the most critical evaluations were given when supervisees' CS experience was <1 year and sessions were infrequent and long in duration.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Our methodological orientation at the time of the study was grounded in a value system and track record (Draper et al, 1999;Jenkins, 1998;Rafferty, Lewis, Mabbett, & Vine, 1996) best articulated by an ethos of action research, which rests on the principle that the best way to improve practice is by collaborative and democratic inquiry (B. Green, personal communication, January 1997).…”
Section: Methodsmentioning
confidence: 99%